ANALISIS KETERSEDIAAN JAGUNG NASIONAL MENUJU SWASEMBADA DENGAN PENDEKATAN MODEL DINAMIK - Panikkai, Sumarni; Nurmalina, Rita; Mulatsih, Sri; Purwati, Handewi (Sekretariat Badan Penelitian dan Pengembangan Pertanian, 2017)
In Indonesia, corn mainly use as feeds in particular for poultry. Sustainable national corn self-sufficiency is an ideal condition for Indonesia which has the availability Â Â natural resources and supporting agro-ecological environment. The gap between supply and demand of corn is still relatively large due to the high demand of corn, especially for feed. To attain national corn self-sufficiency, the Government intervened national corn supply by implementing Â of the national corn self-sufficiency policy. This study aims to analyze the increase of corn extensification and productivity by dynamic system approach. Validation on the built-in model showed that the model was valid. The simulation results showed that before the implementation of corn self-sufficiency policy Indonesia was unable to achieve self-sufficiency, and, on the other hand, after the policy implementation the simulation result showed that the sustainable corn self-sufficiency is attainable. Model simulation results showed that extensification and productivity improvement strategies (combined scenario of increased extensification and productivity) were able to increase the production of corn to as many as 25.85 million tonnes through extensification increase and 26.69 million tons through productivity increase.